The Effects of COVID-19 on Placenta and Pregnancy: What Do We Know So Far? - Yin Ping Wong; Teck Yee Khong; Geok Chin Tan (Diagnostics, 2021)
The current coronavirus disease 2019 (COVID-19) pandemic, caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has inflicted a serious health crisis globally. This virus is associated with a spectrum of respiratory illness ranging from asymptomatic, mild to severe pneumonia, and acute respiratory distress syndrome. Accumulating evidence supports that COVID-19 is not merely a respiratory illness per se, but potentially affects other organ systems including the placenta. SARS-CoV-2 gains access to human cells via angiotensin-converting enzyme 2 (ACE-2). The abundance of ACE-2 on the placental cell surface, especially the syncytiotrophoblasts, could potentially contribute to vertical transplacental transmission to the fetus following maternal COVID-19 infection. Intriguingly, despite the placentas being tested positive for SARS-CoV-2, there are very few newborns that manifest virus-induced diseases. The protective effects of the placental barrier to viral infection, limiting the spread of the virus to newborn infants, remain a mystery. The detrimental role of COVID-19 in pregnancies is largely debatable, although COVID-19 maternal infection has been implicated in unfavorable pregnancy outcomes. In this review, we summarize the pathological features manifested in placenta due to COVID-19 maternal infection that have been previously reported, and relate them to the possible disease manifestation. The potential mechanistic pathways associated with transplacental viral transmission and adverse pregnancy outcomes are also discussed.